An investigation of the psychometric properties of the Geriatric Anxiety Scale (GAS) in an Italian sample of community-dwelling older adults. (2nd September 2018) - Gatti, Alessia; Gottschling, Juliana; Brugnera, Agostino; Adorni, Roberta; Zarbo, Cristina; Compare, Angelo; Segal, Daniel L.
ABSTRACT: Background : The Italian older adult population is increasing and psychiatric problems, such as anxiety among older adults, represent major challenges for public welfare. A strong need exists for instruments specifically developed to assess anxiety among Italian older adults. The Geriatric Anxiety Scale (GAS) is a 30-item self-report questionnaire that evaluates anxiety among older adults and has demonstrated strong psychometric properties in several languages. Objective : The present study aimed to validate an Italian version of the GAS (GAS-I) and to preliminarily investigate its psychometric properties. Method : The translation was performed using a five-stage procedure, following a forward–back process and paying attention to cultural issues. The GAS-I was administered to 231 community-dwelling older adults with other commonly-used questionnaires of anxiety, depression, and quality of life. Results : Results confirmed good psychometric qualities of the questionnaire. Confirmatory factor analyses evidenced a unidimensional structure of the GAS-I, in accordance with other validated versions. Convergent and discriminant validity were highly satisfactory. The three-factor model also provided an acceptable fit to the data. Receiver operating characteristic curve analyses revealed good discriminatory power of the GAS-I. Conclusion : These findings demonstrate that the GAS-I is a reliable and valid self-report questionnaire to measure anxiety among Italian older adults.